Penerapan Pilkada Asimetris Sebagai Upaya Menciptakan Sistem Pemerintahan Daerah Yang Efektif - Ahmad Gelora Mahardika; Sun Fatayati (Indonesian Journal of Humanities and Social Sciences, 2020)
Direct Pilkada as a democratic event often presents problematic regional heads, be it the head of the corruption suspect who was re-elected or the regional head who only won because of his high level of popularity but lack of quality. In the end, many problems in the regions are often not resolved. Regional autonomy, which is expected to be able to produce more developed and quality regions, is collided with the reality and the will of the people who still do not clearly understand the meaning of direct democracy itself. The concept of an asymmetric regional head election system is one solution to overcome this problem. Currently, the asymmetrical system for regional head elections is already in operation, however, it is only applied to a number of regions with special labels. Asymmetrical implementation of Pilkada needs to be applied to all regions in Indonesia. As an indicator in the asymmetric concept, stability in economic growth before the implementation of regional elections or the democracy index can be used to measure the quality of democracy in a region. The research method in this article is normative juridical. The conclusion in this article is that an asymmetrical regional head election system needs to be done to create a more effective regional government.